Learner-centered teaching : putting the research on learning into practice - Doyle, Terry, 1951- (Stylus Pub., 2011)
This book presents the research-based case that Learner Centered Teaching (LCT) offers the best means to optimize student learning in college, and offers examples and ideas for putting it into practice, as well the underlying rationale. It starts from the premise that many faculty are much closer to being learner centered teachers than they think, but don't have the full conceptual understanding of the process to achieve its full impact. There is sometimes a gap between what they would like to achieve in their teaching and the knowledge and strategies needed to make it happen. LCT keeps all of.